15N-Azides as practical and effective tags for developing long-lived hyperpolarized agents. Issue 42 (21st October 2021) - Bae, Junu; Zhang, Guannan; Park, Hyejin; Warren, Warren S.; Wang, Qiu
Abstract : This work demonstrates that 15 N-labeled azides are practical and effective tags for developing long-lived hyperpolarized MRI agents and can offer hyperpolarization lifetimes up to 9.8 min at 1 T and high polarization levels up to 11.6% in water. Abstract : Azide moieties, unique linear species containing three nitrogen atoms, represent an attractive class of molecular tag for hyperpolarized magnetic resonance imaging (HP-MRI). Here we demonstrate ( 15 N)3 -azide-containing molecules exhibit long-lasting hyperpolarization lifetimes up to 9.8 min at 1 T with remarkably high polarization levels up to 11.6% in water, thus establishing ( 15 N)3 -azide as a powerful spin storage for hyperpolarization. A single ( 15 N)-labeled azide has also been examined as an effective alternative tag with long-lived hyperpolarization. A variety of biologically important molecules are studied in this work, including choline, glucose, amino acid, and drug derivatives, demonstrating great potential of 15 N-labeled azides as universal hyperpolarized tags for nuclear magnetic resonance imaging applications.